2011
DOI: 10.1111/j.1468-3083.2011.04160.x
|View full text |Cite
|
Sign up to set email alerts
|

Halo naevi with associated vitiligo‐like depigmentations: pathogenetic hypothesis

Abstract: In this article, we describe in a limited subset of patients with multiple halo naevi discrete depigmentations at distance from halo naevi which may result from a temporary autoimmune process directly linked to the halo phenomenon. This finding illustrates the collateral damage resulting from skin immunosurveillance and may have clinical consequences as the evolution pattern in this subset of patients is less progressive compared with vitiligo. We present clinical data that support this hypothesis and suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 30 publications
(69 reference statements)
1
20
1
3
Order By: Relevance
“…16 Previously, we described a similar mechanism in patients with multiple halo naevi. 17 In this study, we observed a higher prevalence of CMN in patients with vitiligo compared with the control group, although this finding was not significant. However, this might be due to the relatively small number of patients in the control group.…”
Section: Discussioncontrasting
confidence: 65%
“…16 Previously, we described a similar mechanism in patients with multiple halo naevi. 17 In this study, we observed a higher prevalence of CMN in patients with vitiligo compared with the control group, although this finding was not significant. However, this might be due to the relatively small number of patients in the control group.…”
Section: Discussioncontrasting
confidence: 65%
“…[16] identified a subset of halo nevi with additional subtle depigmentations distant to HN and called “halo nevi associated-leukoderma” [16]. In our own study, several depigmented spots were found, especially in the posterior trunk middle related to halo nevi located in the anterior trunk upper (3/22), but the biopsy from spots has been not taken.…”
Section: Discussionmentioning
confidence: 89%
“…Multiple halo nevi was developed by 25-50% of halo nevi patients. 41,42 It involves most commonly compound nevi, although a junctional or dermal pattern is also possible. Both congenital and acquired nevi can be affected.…”
Section: Sutton Nevus (Halo Nevus)mentioning
confidence: 99%